Exotic electronic states in the world of flat bands： From theory to material - Liu, Zheng; Liu, Feng; Wu, Yong-Shi (Chinese physics B, 2014)
It has long been noticed that special lattices contain single-electron flat bands （FB） without any dispersion. Since the kinetic energy of electrons is quenched in the FB, this highly degenerate energy level becomes an ideal platform to achieve strongly correlated electronic states, such as magnetism, superconductivity, and Wigner crystal. Recently, the FB has attracted increasing interest because of the possibility to go beyond the conventional symmetry-breaking phases towards topologically ordered phases, such as lattice versions of fractional quantum Hall states. This article reviews different aspects of FBs in a nutshell. Starting from the standard band theory, we aim to bridge the frontier of FBs with the textbook solid- state physics. Then, based on concrete examples, we show the common origin of FBs in terms of destructive interference, and discuss various many-body phases associated with such a singular band structure. In the end, we demonstrate real FBs in quantum frustrated materials and organometallic frameworks.